Basal and T3-induced ROS Production in Lymphocyte Mitochondria is Increased in Type 2 Diabetic Patients - Anthonsen, S.; Larsen, J.; Pedersen, P. L.; Dalgaard, L. T.; Kvetny, J. (Hormone and Metabolic Research, 2013)
Mitochondrial function, including production of reactive oxygen species (ROS), is important in the pathogenesis of diabetes and its complications. Thyroid hormones are major regulator of these processes. Hence, the aim of this study was to examine the thyroid hormone regulation of ROS production in human lymphocytes in patients with diabetes mellitus type 2 (T2DM). Lymphocytes from 10 controls and 10 persons with T2DM were examined. Mitochondrial membrane potential (MMP) was examined by flow cytometry after staining with MitoTracker Green (MTG). Similarly ROS was measured following staining with carboxy-H2DCFDA. MMP was increased in T2DM patients and T3 stimulation increased MMP in controls [1 398 a.u. (979–4 094) vs. 2 156 a.u. (1 611–15 189), p=0.04, median and quartiles] as well as in T2DM patients [9 167 a.u. (7 387–11 746) vs. 20 274 a.u. (17 183–27 839 p=0.004, median and quartiles]. Basal ROS concentration was increased in lymphocytes from T2DM and T3 significantly stimulated ROS concentration in controls [3 691 a.u. (2 584–6 396) vs. 5 650 a.u. (3 001–7 802) p=0.013, median and quartiles] and in T2DM patients [19 271 a.u. (6 288–25 282) vs. 23 178 a.u. (10 004–28 857) p=0.013, median and quartiles]. The ratio of ROS production related to MMP was significantly higher in T2DM, unstimulated as well as T3-stimulated in T2DM. Unstimulated and T3 stimulated ROS production and MMP were higher in lymphocytes from diabetic patients. An altered balance between ROS production and MMP, favoring ROS production in T2DM patients, was found suggesting that an increased mitochondrial sensitivity for T3 may be a significant factor responsible for increased ROS activity in diabetic patients.
Keywords: diabetes mellitus type 2; thyroid hormone; mitochondria; ROS; MMP